2018
DOI: 10.24275/uam/izt/dcbi/revmexingquim/2018v17n3/guzman
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION AND EVALUATION OF MODERN TRITICALE (X Triticosecale Wittmack ) LINES FOR MALT PRODUCTION AND CRAFT BEER BREWING

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
3
4
0
1
Order By: Relevance
“…In the study by Feng et al [12], a voltage between 0.4 and 0.5 V, fed with brewery wastewater, was obtained, using Pt as catalyst in the cathode, which favored the voltage response. In agreement with this, in studies by Wen et al [13] (180 mL volume, treating beer brewery wastewater) and Yu et al [15] (working volume of 225 mL, single-chamber microbial fuel cells with brewery wastewater), the anode and cathode were connected by a copper wire with an external resistance of 100 Ω. These studies also used Pt as a catalyst and obtained voltages between 0.5 and 0.6 V. Driessen and Vereijken [38], who focused on a serpentine-type microbial fuel cell stack with 40 tubular air cathodes eating brewery wastewater, employed a stack with a usable volume of 10 L, reporting a total stack voltage of 23 V, with averages in each fuel cell of 0.58 and 0.64 V. Similarly, Dong et al [11] obtained average values per fuel cell of 0.6 V in a usable volume of 90 L.…”
Section: Performance Of Mfcs (Stacked)supporting
confidence: 74%
See 2 more Smart Citations
“…In the study by Feng et al [12], a voltage between 0.4 and 0.5 V, fed with brewery wastewater, was obtained, using Pt as catalyst in the cathode, which favored the voltage response. In agreement with this, in studies by Wen et al [13] (180 mL volume, treating beer brewery wastewater) and Yu et al [15] (working volume of 225 mL, single-chamber microbial fuel cells with brewery wastewater), the anode and cathode were connected by a copper wire with an external resistance of 100 Ω. These studies also used Pt as a catalyst and obtained voltages between 0.5 and 0.6 V. Driessen and Vereijken [38], who focused on a serpentine-type microbial fuel cell stack with 40 tubular air cathodes eating brewery wastewater, employed a stack with a usable volume of 10 L, reporting a total stack voltage of 23 V, with averages in each fuel cell of 0.58 and 0.64 V. Similarly, Dong et al [11] obtained average values per fuel cell of 0.6 V in a usable volume of 90 L.…”
Section: Performance Of Mfcs (Stacked)supporting
confidence: 74%
“…For CBW, all three types of acids were present, except for the last day, when only acetic acid was detected (between days 5 and 6), caused by the composition of the actual wastewater itself, which contained organic acids, mostly acetic acid, from beer production [41]. Generally, it was observed that acetate was predominant in the system; the presence of butyric acid (maximum concentration was 205 ± 59 mg L −1 on the first day) and propionic acid (maximum concentration was 95 ± 5 mg L −1 on the second day) were propitiated by the bacterial community; acetate and propionate, two of these acids, made the biggest contributions to the production of energy reported by Yu et al [15], who found the presence of ethanol, acetate, butyrate, and propionate in an MFC fed with real brewery wastewater, which is consistent with the present study.…”
Section: Volatile Fatty Acidsmentioning
confidence: 88%
See 1 more Smart Citation
“…It is identified and selected as the best line suitable for malt production and brewing. Ten triticale lines show protein content (11.97-14.52 %) and carbohydrates (77.24-82.87 %) useful for malt production [12].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…La prediccion del comportamiento funcional de las nuevas proteínas, grasas, fibras y carbohidratos en sistemas específicos requiere de una evaluacion constante para demostrar si dicha proteína puede reemplazar la proteína convencional (Mattil, 1971). A pesar de que el triticale contiene deficiencia de lisina su contenido es mayor que el de los trigos comerciales (Guzmán-Ortíz et al, 2018;Mergoum et al, 2019). En decadas anteriores la investigación se centró en mejorar la capacidad de unión y la solubilidad de la proteina al agua (Ahmedna et al, 1999;Leonova et al, 2021).…”
Section: Introductionunclassified